(untitled) (International Journal of Physiotherapy, 2020)
Background: Goals of Rehabilitation after Traumatic Brain Injury (TBI) focus on preventing complications and improving the level of functional independence. The expectation of TBI survivors and family members following rehabilitation are focused on the quality of outcomes such as reintegration into the community, return to work, and maximal functional capacity. Multiple factors may affect recovery after TBI when interacting with the primary condition and predicting the degree of recovery helps in framing realistic goals. The purpose of this study was to analyze the factors influencing the functional outcome in TBI patients at four months post-injury. Methodology: This observational study was carried out in the Neurosurgery outpatient department when TBI patients returned for review at four months post-injury. 50 TBI patients who were able to follow commands participated in this study. Factors like Admission Glasgow coma scale (GCS), Discharge GCS, Length of Hospitalization, Associated fractures of the upper and lower limb, Co-morbid conditions like Diabetes and Hypertension were obtained from the discharge summary of the patient. Caregiver literacy was obtained from the person who took care of the patient completely. Admission CT scan was graded using the Marshall CT classification. Finally, all these factors were compared to the functional status of the patient evaluated using the Barthel Index. Results: Logistic regression was used to predict the factors affecting the functional outcome. Beta value of Caregiver literacy, Discharge GCS, and Co-morbid conditions was .561, .369 and .234, respectively which influences the functional outcome of TBI patients at four months post-injury. Conclusion: The study concludes that caregiver literacy, Discharge GCS, and Co-morbid conditions influence the functional outcome of TBI patients, which emphasizes the need for awareness and education of the caregiver and along with post-discharge rehabilitation program specific exercises addressing the co-morbid conditions would enhance the recovery.